Promoting Shared Metacognition in Online Learning: The Practices of Distributed Teaching Presence and the Relationships to Cognitive Presence - Ye Chen; Lixuan Chen (Education Sciences)
This study explores the practices of distributed teaching presence (DTP) to promote students’ shared metacognitive responsibilities in online learning. The DTP practices included providing explicit instruction on DTP techniques and guiding students to label their cognitive presence in online discussion. Data were collected through asynchronous online discussion and a questionnaire survey from 53 students enrolled in a graduate-level course at a northeastern private university in the United States. By analyzing the discussion transcripts, students’ cognitive and teaching presences were examined to reveal the influence of the interventions on students’ learning engagement. Both qualitative and quantitative analysis were conducted to analyze the 2557 messages created by 53 students. The results showed that guiding students to use DTP techniques credibly improved students’ teaching and cognitive presence. We also found that students’ teaching presence behaviors were positively associated with peers’ cognitive presence and their own higher-level learning. The implications for research and practices in designing and facilitating shared metacognitive learning experience are also discussed.